Nghiên cứu sự tác động của hiện tượng “buồng vang thông tin” (echo chamber) đối với thế hệ Gen Z - Phạm Nguyễn Phúc Toàn, Phạm Nguyễn Phúc Toàn; Phạm Văn Luân, Phạm Văn Luân (Tạp chí Giáo dục, 2026)
In the context of education being heavily influenced by the digital environment and online media platforms, the issue ofinformation access and the development of critical thinking skills among learners is attracting significant research attention. Echo chamber - the phenomenon where users primarily receive information that aligns with their pre-existing viewpoints - is recognized as a common occurrence in the digital media space, especially among young people of Generation Z. With high social media usage and frequent interaction with content recommendation systems, Gen Z tends to repeatedly encounter similar information sources, which can influence how they form perceptions and evaluate information. This article employs a qualitative research approach to synthesize and analyze domestic and international studies related to the mechanism of echo chamber formation and its impact on the behavior and cognition of Gen Z. Based on the synthesized results, the article proposes three intervention directions: enhancing digital media education for learners, considering adjustments to the operation of content recommendation algorithms, and encouraging the development of online spaces that promote multi-directional information exchange. These suggestions provide a reference basis for developing educationalsolutionsthatsupport Vietnamese learnersin developing critical thinking in the digital environment.